FACTORS INFLUENCING THE AUDITOR’S DETECTION AND REPORTING OF TAX EFFICIENT SUPPLY CHAIN MANAGEMENT - Khudhair, Dheyaa Zamil; Abdul-Hussein Raji, Ali; Al-Zubaidi, Firas Abbas (International Journal of Supply Chain Management, 2019)
In this paper, while emphasizing on the importance of applying the concept of supply chain management in the service sector, its application in the tax process of the country was discussed and discussed. At first, two tax identification and tax information processing chains were defined. Then, based on the experiences and principles governing the supply chain management in the automotive industry, the tax supply chain development model was proposed. Taxation is an important financial instrument of financial policy instruments because it is one of the important sources of revenue for the general budget of the state, which is the basis for the design and planning of fiscal policy. Accordingly, the main aim of the research is to state and analyze the factors that influence the auditor's discovery of tax evasion practices determining them by a group of factors divided into four groups commensurate with the nature of the external audit. The first group includes the factors related to the auditor. The second group includes the factors related to the management of the company. The third group includes the factors related to the professional publications. The fourth group includes religious and social factors. To the objectives of the study, the researchers designed a questionnaire for the purpose of collecting data and distributing them to the target sample of the research which were auditors of accounts in Iraqi audit firms and companies. To analyze the data of the study and test the hypotheses of the research, a number of tests were used in the Statistical Package for Social Sciences (SPSS). The study reached to several conclusions, the most important of which is that the process of discovering tax evasion practices by the auditor is influenced by several factors which reflect the following arrangement according to the effect: factors related to the management of the company, as well as the auditor, as well as factors related to professional issues, in addition to the absence of influence of religious and social factors. The research ends with a number of recommendations, the most important of which are: the necessity of taking care of the scientific and practical rehabilitation of the auditors so as to improve their performance, the need to seek the issuance and updating of Iraqi professional standards and their revision and development, the need to seek the issuance and revision of Iraqi professional standards and to revise and develop them in accordance with the changing requirements of auditing, and finally issuing a local audit standard and guide for financial fraud, including tax evasion practices.